2009
DOI: 10.1159/000245906
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Evolution in Domestic Bovids as Revealed by Chromosome Banding and FISH-Mapping Techniques

Abstract: The present review summarizes the basic cytogenetic information available pertaining to the most important Bovidae species, namely cattle, buffalo, sheep and goat, with the aim of tracing their evolutionary relationships and to provide – for the first time – the hypothetical ancestral karyotype of the Bovinae-Caprinae subfamilies, also in relation to the other nondomestic species which are included in this important taxonomic family. Evolution of the Bovinae-Caprinae autosomes and gonosomes is discussed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 111 publications
5
78
0
Order By: Relevance
“…To assess the reliability of the chromosome anchoring, we examined 28 goat genes that have been assigned to a specific chromosomal location 21 (Supplementary Table 5). The chromosome assignments of all 28 genes were consistent with our results.…”
Section: A R T I C L E Smentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the reliability of the chromosome anchoring, we examined 28 goat genes that have been assigned to a specific chromosomal location 21 (Supplementary Table 5). The chromosome assignments of all 28 genes were consistent with our results.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…6), even though the X-chromosome linkage group is usually conserved in placental mammals 21 . The same rearrangements were observed on the X chromosomes when comparing them to both cattle genome assemblies (UMD_3.1 and Btau_4.0).…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Frequency of FITC signals (double or single signals in both or single chromosomes or chromatids) varies from 45% in both cattle and river buffalo with CYP1A1 to 23% in sheep with AHR. All six loci map in homologous chromosomes and chromosome bands of the four species, as expected given the high degree of autosome homologies among bovids (reviewed in Iannuzzi et al 2009), although a simple translocation event differentiated "bovinae" chromosomes 9 and 14 from homologous chromosomes of "caprinae" (and remaining bovid subfamilies) (reviewed in Iannuzzi et al 2009). Corresponding human locations HGNC ( http:// www.genenames.org/) of the six genes are in agreement with comparative mapping data between bovids and humans (Table 1).…”
mentioning
confidence: 63%
“…A combination of banding and FISH-mapping techniques with specific molecular markers mapping proximally to BTA29 and three SAT DNA (SAT I, SAT III and SAT IV) demonstrated that also the rob(1;29) of cattle originated by complex chromosomal rearrangements: a centric fusion translocation is followed by a pericentric inversion or chromosome transposition of a small proximal region of the p-arm (BTA29) to the proximal q-arm (BTA1) of the translocated chromosome (Chaves et al 2003;Di Meo et al 2006;Iannuzzi et al 2009). In the BGA1, the paracentric inversion occurring in the qarm (homoeologous to BTA1) has radically differentiated this biarmed chromosome from that of the rob(1;29) of cattle.…”
Section: Resultsmentioning
confidence: 99%
“…As with other bovidae, chromosome studies indicate that the gaur evolved from a wild ancestor, differentiating the domestic taurine and zebu cattle (Wurster and Benirschke 1968;Buckland and Evans 1978;Gallagher and Womack 1992;Iannuzzi et al 2009;Da PaixaoScavone et al, 2000). Centric fusion between chromosomes 2 and 28 of the ancestral cattle karyotype gave rise to the Indian gaur karyotype (2n = 58), consisting of 27 pairs of acrocentric and one pair of submetacentric autosomes (Gallagher and Womack 1992;Mastromonaco et al 2004).…”
Section: Introductionmentioning
confidence: 98%